Performance evaluation of CPF approved trustee stocks. - Ong, Ai Ling. (2008)
The main objective of this study is to provide a better understanding of the performance of CPF approved trustee stocks and their difference from non-trustee stocks.This study is divided into two main sections. In the first, we will use the DBS CPF Approved Trustee Stocks Index as a proxy to trustee stock performance. The index is compared against the market index, SES All-Singapore Index. Risk return ratios such as Coefficient of Variance, Sharpe Index and Treynor Index are then used to compare the performance of the two indices. In the second section this study, 64 trustee stock companies were chosen and their financial ratios from year 1994 to 1996 were collected.